Napoleon, Bourses, and Growth in Latin America - Ross Levine (Inter-American Development Bank, Office of the Chief Economist, 1997)
The value of equity market transactions in emerging economies soared from about 2 percent of the world total in 1986 to 12 percent in 1996. This boom was accompanied by an explosion of international capital flows, especially flows into developing country stock markets. Moreover, while equity flows were a negligible part of capital flows to emerging markets a decade ago, equity flows now represent about 20 percent of private capital flows to developing nations.
Keywords: 330; Wirtschaftswachstum; Aktienmarkt; Finanzmarktregulierung; Lateinamerika